Controlling as an Information Source in Risk Management Process - Dynowska, Joanna; Bartoszewicz, Anna (Olsztyn Economic Journal, 2014)
An increasingly visible tool in identifying risk is controlling. Its tasks include collecting, processing, and analyzing information. Thus, in the stage of identifying the risk management process, controlling should supply management with information regarding the impacts of risks on particular departments of the company. The purpose of this article was to emphasize the role of controlling in the risk management process within an organization. This objective was achieved through a study of literature from research conducted in the field. Over the course of this study, the value of controlling and its role in the risk management process were revealed. Also, the role of budgeting was shown to be a key tool of controlling in the process of risk management. The implementation of controlling in a company permits full use of information and enables the use of modern management techniques, thereby facilitating making good decisions to rectify or mitigate risk for a specific organization or unit.